The BioSUD Biobank as a genomic resource for substance use disorders in Italy - Raffaella Maria Ribatti; Luciana de Gennaro; Alessia Daponte; Danilo Cozzoli; Maria Rita Quaranta; Angelo Ostuni; Margherita Casanova; Vincenza Ariano; Vincenzo Leone; Francesco Perrone; Salvatore Della Bona; Angela Lacalamita; et al. (Scientific Reports)
Abstract Substance Use Disorders (SUDs) are a significant public health concern with complex etiologies involving genetic, environmental, and psychological factors. Here, we present BioSUD, a biobank that, by integrating genomic data with comprehensive phenotypic assessments, including sociodemographic, psychosocial, and addiction-related variables, was designed to investigate the etiology of SUDs within the Southern Italian population. We assessed a cohort of 1,806 participants (1,508 controls and 298 individuals with SUD diagnosis). Genomic analyses of the newly generated genotypes showed a predominantly Southern Italian ancestry for the BioSUD cohort. Admixture analysis reveals a complex history of genetic admixture in Southern Italian populations, exhibiting Southern European, African, and other ancestries. This results in significant genetic variation, potentially limiting the applicability of translational studies primarily based on Northern European ancestries. From a social and psychological perspective, individuals with SUDs exhibited lower socioeconomic status, increased exposure to adverse experiences, and compromised familial and peer relationships relative to controls. These results show that the BioSUD cohort is valuable for studying SUD-associated complex behavioral traits.